Alienation in Adolescence in J.D. Salinger's The Catcher in the Rye (Journal of the College of Languages (JCL), 2013)
Alienation is a feeling that inflicts people especially adolescents due to certain reasons. As they grow up, adolescents tend to face certain psychological disturbances. They somehow feel indifferent to their surroundings and hence it would be quite hard for them to express their notions in the reality world they live in. So they either rebel against society and become aggressive members or they might console themselves in an alienated world that they create in their minds. This paper depicts J.D. Salinger's (1919-2010) novel The Catcher in the Rye where its protagonist, Holden Caulfield, is an adolescent who feels there is no linkage or connection with the traits of his society. He is a teenager who portrays his innermost concerns and disillusionment toward a world that he feels unable to fit in. He likes to take decisive actions but feels helpless since his resolutions are thwarted by certain factors of life, e.g., parents, customs and social codes. He feels distant in his relationships with others and absolutely baffled about the uncertainty of his future. Holden Caulfield clings to the innocence of the childhood world and feels total empathy toward children because they still have not been corrupted and shaped according to the mores of society. Holden realizes that growing up, the maturing process, indicates that he should assume responsibility in a world where he thinks only superficial and insignificant issues occur. He like many others seems to have difficulty fitting into a world that seems disintegrated and filled with defacement. Holden is caught in the disturbed transition of his life-from the state of childhood into adulthood. He thus faces anxiety and alienation and wants to detach himself from all the false values surrounding him. Holden's therapy at the hospital after his nervous collapse due to his alienation, makes him realize that life consists of limitless ambiguities. It is a mixture of the good and the bad. Hence, part of Holden's therapy is his realization that he cannot remove all the impurity and retrogression, but instead he must become part of the society that he rejects. His inference, by the end of the novel, is that life's mystery can only be solved and perceived if one fathoms the mistakes of others through the love and understanding of mankind.